Nilo’s: a história da arte egípcia integrada ao design de interiores e à gastronomia - SILVA, Sabrina Gonçalves de Carvalho (285, 2023)
O trabalho vigente tem como objetivo projetar um restaurante que se localiza na Zona Sul da cidade de São Paulo, especificamente na cidade Jardim na Rua Oscar Freire. O projeto é um restaurante que busca a releitura de aspectos egípcios sofisticados chamado – Nilo’s, o mesmo conta com cores e materiais que buscam a identidade egípcia sofisticada na qual poucos a conhecem, trazendo assim a diferença dentro do mercado na cidade de São Paulo. Idealizando por um lado técnico, pensando em materiais que se adaptem a estética antiga porém mantendo os aspectos sofisticados da mesma, assim estudando como a importância da temática posa se casar definitivamente com o tema especificado, como exemplo temos móveis com materiais de pedras, e elementos como os desenhos de hieróglifos nas paredes, também a caracterização da presença de pedras no piso, porém atrelado a modernidade para que a releitura seja feita de forma mais agradável para a estética e o tema.

The current work aims to design a restaurant located in the South Zone of the city of São Paulo, specifically in the city of Jardim on Rua Oscar Freire. The project is a restaurant that seeks to reinterpret sophisticated Egyptian aspects called – Nilo’s, it has colors and materials that seek the sophisticated Egyptian identity in which few know it, thus bringing a difference within the market in the city of São Paulo. Idealizing on a technical side, thinking about materials that adapt to the ancient aesthetic but maintaining its sophisticated aspects, thus studying how the importance of the theme can definitively marry with the specified theme, as an example we have furniture with stone materials, and elements such as the hieroglyphic drawings on the walls, also the characterization of the presence of stones on the floor, but linked to modernity so that the reinterpretation is done in a more pleasant way for aesthetics and the theme.

The current work aims to design a restaurant located in the South Zone of the city of São Paulo, specifically in the city of Jardim on Rua Oscar Freire. The project is a restaurant that seeks to reinterpret sophisticated Egyptian aspects called – Nilo’s, it has colors and materials that seek the sophisticated Egyptian identity in which few know it, thus bringing a difference within the market in the city of São Paulo. Idealizing on a technical side, thinking about materials that adapt to the ancient aesthetic but maintaining its sophisticated aspects, thus studying how the importance of the theme can definitively marry with the specified theme, as an example we have furniture with stone materials, and elements such as the hieroglyphic drawings on the walls, also the characterization of the presence of stones on the floor, but linked to modernity so that the reinterpretation is done in a more pleasant way for aesthetics and the theme.
Keywords: Arquitetura de interiores; Design; Serviços de alimentação; Produção Cultural e Design